Simultaneous and visual detection of multiple dopes by an aptamer/AuNPs sensor. (23rd September 2022) - Fu, Xuancheng; Gou, Miaomiao; Zhang, Yong; Su, Hao; Zhao, Haotian; Liu, Chang; Han, Jing
Abstract : Through introducing multiple aptamers in a suitable ratio, we achieved the simultaneous and visual detection of three dopes in one sensor. Abstract : Point-of-care testing (POCT) has exhibited broad applications owing to its rapid on-site detection capability under resource-limited conditions. However, most POCT sensors can only detect single substance in each assay, which does not meet the requirements of simultaneous multi-components analysis in most cases. Herein, we report a simple POCT sensor for simultaneously analyzing multiple dopes in minutes. This sensor is composed of gold nanoparticles (AuNPs) assembled with several aptamers. The coating of aptamers on the surface of AuNPs prevents nanoparticles from aggregating in a high-salt environment. In the presence of dopes, the stronger interaction between aptamers and dopes induces the stripping of aptamers from the AuNPs, following the AuNP aggregation in high-salt conditions which further results in a significant color change of the solution. Introducing multi-aptamers in a suitable ratio, we achieved the simultaneous and visual detection of three dopes in one sensor. The linear ranges were determined as 0.1–10 μM for dexamethasone, 0.5–100 μM for salbutamol, and 0.05–10 μM for ractopamine, with detection limits of 53 nM, 130 nM, and 11 nM for the above targets, respectively. The feasibility of this method in practical application was also confirmed via blood and urine samples. Compared with traditional targeting single dopes POCT sensors, this multi-dopes detecting sensor better matches the real demands required during dopes testing. Meanwhile, this label-free approach for simultaneous multi-component detection broadens the application of POCT towards simultaneous multi-target analysis.